Surgery for Complications of Acute Pancreatitis-A Case Series - Islam, Sardar Mohammad Rezaul; Sarkar, Shah Alam; Paul, Debabroto; Rahman, Mushfiqur (British Journal of Healthcare and Medical Research, 2024)
Sixteen patients operated for complication of acute pancreatitis for a period of 5 years. We drained 4 infected pancreatic ascites, 3 hemorrhagic pancreatitis. We performed 6 Roux Y cysto-jejunostomy for pseudocystof the pancreas. We managed one patient with ruptured Walled Off Necrosis (WON) by 2 staged procedures. Initially laparotomy, debridement of the infected necrosis and external drainage was done. After 6 weeks permanent internal drainage was done by Roux-Y Cysto-jejunostomy for persistent pancreatic fistula. 2 patients with walled off necrosis had debridement only. All patients recovered successfully.